A influência das formações continuadas no cotidiano dos professores de Educação Física - Neves, Cláudia Pereira das; Hernandez Botelho, Vivian; Silva, Patrícia da Rosa Louzada da; Pinheiro, Eraldo dos Santos (2020)
This study aimed to investigate the continuing education offered by the Municipal Education Department (SMED) of Pelotas, in partnership with the Higher School of Physical Education of the Federal University of Pelotas (ESEF/UFPel), as a possibility of professional improvement of its participants. This is a qualitative study developed with four Physical Education teachers from public schools in Pelotas, in Rio Grande do Sul, which met the criteria of having participated in the continuous training courses of rugby, hockey, handball and baseball offered by SMED, in partnership with ESEF/UFPel, in 2017 and 2018. The instrument used to collect the information was a semi-structured interview applied individually to the teachers. The main results found include the importance of continuing education related with knowledge and application of sports that were hitherto unconventional in schools, and the influence of training in stimulating promotion and participation in school sports festivals. Therefore, through the training it was possible to provide a new meaning of teaching sports in the school environment, by promoting unconventional sports, as well as providing spaces for school competition.
O presente estudo teve como objetivo investigar a formação continuada, ofertada pela Secretaria Municipal de Educação (SMED) de Pelotas em parceria com a Escola Superior de Educação Física da Universidade Federal de Pelotas (ESEF/UFPel), como possibilidade de aprimoramento profissional de seus participantes. Trata-se de um estudo de natureza qualitativa, desenvolvido com quatro professores concursados de Educação Física da rede pública municipal de Pelotas, no Rio Grande do Sul, que atenderam ao critério de ter participado das formações continuadas de rugby, hóquei, punhobol e beisebol ofertadas pela SMED em parceria com ESEF/UFPel nos anos de 2017 e 2018. O instrumento utilizado para coleta das informações foi uma entrevista semiestruturada aplicada individualmente aos professores. Como principais resultados encontrados destacam-se a importância da formação continuada em relação ao conhecimento e aplicação de modalidades esportivas até então não convencionais nas escolas e a influência da formação no sentido de um estímulo à promoção e participação em festivais esportivos de cunho escolar. Portanto, através das formações, foi possível propiciar uma ressignificação do ensino do esporte no ambiente escolar, ao instigar o fomento de modalidades esportivas não convencionais, assim como a oferta de espaços para competição escolar.
Keywords: Sports; Schools; Perception; Experiences; Esportes^lpt; Escola; Percepção; Experiências